Effusion of a dilute gas revisited: Van Kampen’s expansion - Schat, Carlos Luis; Abramson, G.; Wio, Horacio Sergio (Comisión Nacional de Energía Atómica; Argentina)
Fil: Schat, Carlos Luis Comisión Nacional de Energía Atómica; Argentina